2015
DOI: 10.1016/j.ijcard.2014.10.155
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic interval training and continuous training equally improve aerobic exercise capacity in patients with coronary artery disease: The SAINTEX-CAD study

Abstract: Contrary to earlier smaller trials, we observed similar improvements in exercise capacity and peripheral endothelial function following AIT and ACT in a large population of CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
286
6
23

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 248 publications
(334 citation statements)
references
References 38 publications
(31 reference statements)
16
286
6
23
Order By: Relevance
“…In recent years, the treatment effects of HIT, which is composed of low‐level exercise with short bouts of high‐intensity exercise at 90% to 95% of peak heart rate, were tested prospectively in different patient populations. Contrary to the promising results of smaller trials, the SAINTEX‐CAD (Study on Aerobic Interval Exercise Training in CAD Patients) failed to show an additional improvement in peak oxygen uptake and endothelial function with HIT compared with MCT in patients with CAD 116. In patients with heart failure, HIT was not associated with additional reverse left ventricular remodeling or peak oxygen uptake compared with MCT in the SMARTEX‐HF (Study of Myocardial Recovery After Exercise Training in Heart Failure) trial 77.…”
Section: Exercise Prescriptionmentioning
confidence: 73%
See 1 more Smart Citation
“…In recent years, the treatment effects of HIT, which is composed of low‐level exercise with short bouts of high‐intensity exercise at 90% to 95% of peak heart rate, were tested prospectively in different patient populations. Contrary to the promising results of smaller trials, the SAINTEX‐CAD (Study on Aerobic Interval Exercise Training in CAD Patients) failed to show an additional improvement in peak oxygen uptake and endothelial function with HIT compared with MCT in patients with CAD 116. In patients with heart failure, HIT was not associated with additional reverse left ventricular remodeling or peak oxygen uptake compared with MCT in the SMARTEX‐HF (Study of Myocardial Recovery After Exercise Training in Heart Failure) trial 77.…”
Section: Exercise Prescriptionmentioning
confidence: 73%
“…The authors, therefore, speculated that the total energy spent on exercise training is more important to increasing peak oxygen uptake than exercise intensity 117. The number of serious adverse events with HIT was low and did not differ from MCT in patients with CAD 116, 118. In patients with heart failure, serious adverse events were numerically higher with HIT than with MCT.…”
Section: Exercise Prescriptionmentioning
confidence: 99%
“…One possible explanation for this deviation from previously documented benefits is that average peak HR was relatively high in the MICT group compared with prior trials (80% of predicted). 58 Similarly, the SMARTEX Heart Failure Study, a multi-center RCT involving 261 patients, failed to find a benefit from HIIT in comparison to MICT. 59 However, control of ET intensity in different cohorts was imprecise; those in the ET cohort had only 15 out of 77 ET sessions at an intensity consistent with their HIIT protocol; and of 65 patients in the MICT group, 33 exercise at higher than prescribed intensity.…”
Section: Role Of Exercise Intensitymentioning
confidence: 99%
“…13,[16][17][18] Wisloff, et al reported that improvement of peak oxygen uptake was greater in HIIT as compared with moderate aerobic training in patients with heart failure after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%